Verletzlichkeit und Personalität in der Demenz (Nomos Verlagsgesellschaft mbH & Co. KG, 2024)
This book examines the relationship between personhood and vulnerability in dementia from a phenomenological–anthropological research perspective. The disease poses existential challenges to patients affected by it and their social environment in private, nursing and medical settings. Therefore, in interdisciplinary contributions, this study explores the question of how stronger consideration of the bodily constitution of the human being and its existential vulnerability can contribute to both improved practical handling of dementia patients and clarification of the relationship between personhood, vulnerability and dementia as a whole.With contributions byMarion Bär | Erik Norman Dzwiza-Ohlsen | Thomas Fuchs | Regine Kather | Andreas Kruse | Ralph Kunz | Hans-Martin Walter Rieger | Daniela Ringkamp | Sebastian Ritz | Magnus Schlette | Eric Schmitt | Christiane Schrader | Jan Sonntag | Christian Tewes | Charlotte Uzarewicz